Towards a Deeper Understanding of Strategic Management Factors in International Non-Governmental Organizations - Xue Zhang; Raafat George Saadé (Administrative Sciences)
International activities by all NGOs have become ubiquitous. Therefore, international non-governmental organizations (INGOs) are significantly and gradually increasing their international influence shaping a new paradigm for global affairs ranging from human aid to digital governance. In this study, we delve into the literature and connect with professionals to get a deeper understanding of how strategic management is addressed and perceived in INGOs. The paper is composed of two parts, namely a comprehensive literature review followed by a pilot survey-based empirical study, to assess and validate relevant constructs/factors in the context of INGOs. The survey methodology approach was used to assess factors using exploratory factor analysis (EFA). Outcomes from the literature review were cross-examined against the EFA to guide the categorization of factors vis-à-vis new findings. Twelve validated questions relevant to our context were adapted and composed in the survey. EFA resulted in the significant regrouping of items into three factors. We therefore reformulated the constructs in the INGO context. These constructs are strategic structures, human capital, and change management. Strategic constructs represent the traditional strategic management theory. Change management was shown to be a strong factor for the adequate setup and management of strategic structures, and human capital represents a new factor specific to INGOs.